EFECTIVENESS OF TRAINER KITS IN ADVANCED ELECTRONICS LEARNING FOR DEVELOPING COGNITIVE ABILITIES IN PHYSICS EDUCATION: A SYSTEMATIC LITERATURE REVIEW - Rona Pinta Uli Debata Raja; Nehru Nehru; Jules Nurhatmi (Physics and Science Education Journal (PSEJ), 2025)
This study aims to conduct a Systematic Literature Review (SLR) regarding the effectiveness of trainer kits in Advanced Electronics learning in the Physics Education Study Program at a university, specifically in developing students' skills in using the trainer kits. The SLR method was used to collect, analyze, and synthesize the results of similar published studies. Data were collected from indexed journal documents with e-ISSNs through a Google Scholar search using the Publish or Perish application. Inclusion criteria were applied to filter the data population, focusing on the effectiveness of trainer kits in improving students' skills in operating the kits, resulting in a total of five national journal articles used as samples. The synthesis results indicate that the effective use of trainer kits integrated into Advanced Electronics courses contributes significantly to the improvement and development of students' technical skills in assembling, measuring, and analyzing circuits using the trainer kits. This study contributes to the development of physics education by providing an empirical basis for the importance of integrating modern technology-based learning media (trainer kits) to achieve optimal technical and operational learning outcomes at the higher education level